Perubahan Sosial Pasca Penetapan Ibu Kota Nusantara (IKN) pada Masyarakat Pesisir Samboja Kutai Kartanegara Kalimantan Timur - Darmasetiadi, Doni; Ningsih, Etik Sulistiowati; Oktawati, Nurul Ovia (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of the Samboja coastal area is expected to bring about social changes. These changes will not recur in the existing behaviors within the community. This study was conducted to identify the social changes occurring in the Samboja coastal area and to explain the social impacts that have been felt after the establishment of the Capital City of Nusantara (IKN). The research method used is descriptive qualitative. Data collection techniques were conducted through interviews. The results of the study indicate that the social changes that have occurred have not been fully felt in the social structure and culture of the Samboja coastal community. Based on structural functional analysis, it is known that the social changes occurring in the Samboja coastal area manifest as a latent dysfunction condition because many expectations have not been realized as planned. Many parties' involvement is still considered insufficient. Furthermore, the social changes in the Samboja coastal area have led to a non-functional condition in the development of the tourist area through the privatization of the beach, which was previously open access. From a structural functional perspective, the condition of the Samboja coastal community has led to a phenomenon of anomie with a tendency towards ritualistic responses.